Descriptive study of pregnant women's knowledge level about high-risk pregnancy - Ferdina, Cucun Setya; Christiana, Elisa; Zainab, Zainab; Himawati, Ernia Haris (Science Midwifery, 2026)
Pregnancy is a physiological process, beginning with egg fertilization and culminating in child birth, although pregnancy is a natural process, not every pregnancy proceeds without problems. Some women encounter difficulties that could lead to pregnancies with a high risk. The objective of this research is determining the degree of knowledge expectant women have on high-risk pregnancies. For this investigation, a descriptive research methodology was used. The participants comprised 41 pregnant women chosen using overall sampling techniques. The main instrument used to gather data was a questionnaire. Uni-variate methods were used to conduct data analysis. According to the results, most participants lacked enough knowledge regarding high-risk pregnancies; 36 people (88%) displayed little understanding; only 4 individuals (10%) had great understanding; and only one person (2%) was fairly informed. Regarding participant demographics, almost all were in their twenties to early 30s; nevertheless, many still showed inadequate knowledge. Nearly all participants in every evaluated subject matter showed a low degree of knowledge. The study finds that awareness of high-risk pregnancies among pregnant women is still fairly low, therefore stressing the need of better and more enduring maternal health education programs.